Flavonol triglycosides of leaves from Maytenus robusta with acetylcholinesterase inhibition. (March 2017) - Sousa, Grasiely F. de; Aguilar, Mariana G. de; Takahashi, Jacqueline A.; Alves, Tânia M.A.; Kohlhoff, Markus; Vieira Filho, Sidney A.; Silva, Grácia D.F.; Duarte, Lucienir P.
Graphical abstract: Highlights: Methanol extract of leaves from Maytenus robusta was investigated. Two new flavonol glycosides were isolated. Their structures were established by spectroscopic data. In vitro assays demonstrated significant AChE inhibition for flavonoids1 and2 . Abstract: Although Maytenus robusta aqueous infusions of leaves are used in Brazilian traditional medicine for stomach disease treatment, only a few chemical studies of this species are found in literature. The phytochemical investigation of methanol extract from M. robusta leaves yielded the known compound kaempferol (3 ) and two new flavonol glycosides: kaempferol-3- O -β-d -glucopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)-β-d -glucopyranoside (1 ) and quercetin-3- O -β-d -glucopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)-β-d -glucopyranoside (2 ). The chemical structures of1 and2 were elucidated by 1D/2D NMR, ESI–MS and ESI–MS 2 spectral data. It is the first time flavonoids have been reported from M. robusta . Flavonols 1 and2 showed 66% and 80% acetylcholinesterase (AChE) inhibition, compared to 93% of the standard eserine, by the Ellman's method. These substances are one of the few active flavonols linked to a trisaccharide chain in the literature presenting this activity, and contribute to the screening for new types of natural AChE inhibitors.